Eficacia de los azoles en el tratamiento de la Leishmaniasis Cutánea (2016)
standard treatment of cutaneous leishmaniasis has many limitations associated with adverse effects, contraindications and high cost, for this reason have been explored other therapeutic options as the azole compounds.